Uniportal video‐assisted thoracoscopic left S4 anatomical segmentectomy - Song, Nan (Thorac Cancer, 2019)
Uniportal video‐assisted thoracic surgery (VATS) segmentectomy is a demanding technique but is safe and feasible in selected patients and confers favorable efficacy. It presents an acceptable alternative to conventional VATS. Lingulectomy is usually performed with left S4 + S5 segmentectomy. This report describes a case of uniportal VATS of left S4 anatomical segmentectomy alone.